Analisis Penerapan Standar Operasional Prosedur (SOP) Pengolahan Makanan Banquet di Hot Kitchen Hotel Aria Centra Surabaya - Orienta Zubaidah; I.F Romadhoni; Lilis Sulandari; Niken Purwidiani (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research was to find out the analysis of the application of standard operating procedures (SOP) for food processing at the Aria Centra Hotel Surabaya which has a very important role in an industry, one of which is the hospitality industry as a guide or reference for staff to work consistently and with standards. The data collection technique used (1) interviews to find out the application of food processing procedures and the implementation of these procedures: and (2) documentation to find out the analysis of the implementation of standard operating procedures (SOP) for banquet food processing at the Hot Kitchen Hotel Aria Centra Surabaya, an overview of the company and worker data. Data collection was carried out in July-December 2022. The results of this study were an analysis of the application of standard operating procedures (SOP) for banquet food processing at the Hot Kitchen Hotel Aria Centra Surabaya which included (1) standard operating procedures for handling banquets; (2) implementing a banquet menu; (3) material procurement system for banquet ordering needs; (4) standard operating procedures (SOP) for foodstuffs; (5) preparation of banquet materials and tools; (6) strategies to minimize errors in standard operating procedures (SOP) for handling banquets; (7) constraints and solutions in banquet handling. Based on these results it can be concluded that the analysis of standard operating procedures (SOP) for banquet food processing at the Hot Kitchen Hotel Aria centra Surabaya required various stages in handling it.